Time’s arrow and irreversibility in time-asymmetric quantum mechanics - Castagnino, Mario Alberto G. J. (2005)
The aim of this paper is to analyze time‐asymmetric quantum mechanics with respect to the problems of irreversibility and of time’s arrow. We begin with arguing that both problems are conceptually different. Then, we show that, contrary to a common opinion, the theory’s ability to describe irreversible quantum processes is not a consequence of the semigroup evolution laws expressing the non‐time‐reversal invariance of the theory. Finally, we argue that time‐asymmetric quantum mechanics, either in Prigogine’s version or in Bohm’s version, does not solve the problem of the arrow of time because it does not supply a substantial and theoretically founded criterion for distinguishing between the two directions of time.